Sucesión de la taxocenosis de ácaros en la hojarasca de peumo (Cryptocaria alba) y boldo (Peumus boldus) en descomposición - Salazar Martínez, Ana Ernestina (1998)
The purpose of thís paper is to estímate the successional pattern of the acarífauna associated to litter decomposition of peumo (Cryptocaria alba) and boldo (Peumus boldus). The litterbag method was used to study the decomposítion of leaves and the acarifauna was extracted in Berlese funnels from the litter contained in the bags. The litter of the forest floor was used as witness. Fluctuation patterns of abundance and morphospecific diversity differed between litterbags and witness litter, and was interpreted as successional changes. Species of Gamasida were important invaders of litterbags from the first Winter and showed tendence to leave it when the decomposition process advanced. Species of Oribatida presented an inverse pattern. Species of Actinedida and Acaridida showed a variable pattern which reflects its greater capacity for response to environmental changes. Tydeidae sp. (Actinedida), Ascidae sp. (Gamasida), T. putrescentiae (Acaridida), and Oppia sp. 1 (Oribatida) were associated with the first stages of litter decomposition. Bdellidae sp., Stigmaeidae sp. (Actinedida), Suidasia sp. (Acaridida), Oppia sp. 2, Hemileius sp., Totobates sp. y Scheloribates sp. 1 (Oribatida) were characteristic morphospecies of the last stages. Acari tend to colonize first the boldo's litterbags; this is in relation with the morphological characteristic of leaves and may explain its greater initial velocity of decomposition.